Analisis Pertanggungjawaban Keuangan Pada Balai Penyuluhan Pertanian (BPP) Kecamatan Sengah Temila - Yessi Wilda; Reni Dwi Widyastuti; Rina Mayasafitri (Jurnal Akuntansi, Auditing dan Investasi, 2025)
This research is motivated by the importance of accountability and transparency in budget management at the Agricultural Extension Center. The problem that occurs is the delay in submitting accountability reports (SPJ) which impacts the next budget submission. This study aims to analyze the financial accountability system at the BPP of Sengah Temila District, as well as identify supporting and inhibiting factors in its implementation. The method used is descriptive qualitative through observation, interviews and documentation studies. The results of the study indicate that the financial accountability system is in accordance with the rules, starting from management to reporting of Financial Accountability. Supporting factors include the number of human resources, the existence of activity plans and budgets, the existence of disbursement reports and a good relationship between the BPP of Sengah Temila District and the Department of Agriculture, Fisheries and Food Security of Landak Regency. While inhibiting factors include the majority of human resources majoring in agriculture and no accounting majors, limited infrastructure, unstable internet, delays in budget receipts to the BPP account.